Water-based polymer emulsion stabilized fiber aeolian sand macadam base material and preparation method thereof

By adding basalt fibers and wind-abundant sand to the water-based polymer emulsion stabilized fiber, the three-dimensional framework is formed, which solves the problems of easy peeling of water-based polymer emulsion and high manufacturing cost, and achieves high temperature and low temperature of the material Performance improvements and cost reductions extend road life.

CN119263694APending Publication Date: 2025-01-07GEZHOUBA GROUP FOUND ENG +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411461797.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing water-based polymer emulsion stabilized gravel base materials are prone to peel off at high and low temperatures, and have high manufacturing costs, resulting in road damage and increased costs.

Method used

Use water-based polymer emulsion to stabilize fiber wind-abundant sand gravel base material, add basalt fibers and wind-abundant sand, and uniformly disperse the fibers to enhance tensile, shear and crack resistance, and dilute the solution and graded gravel. Optimized preparation method for optimal moisture content, forming a three-dimensional skeleton to lock in the water-based polymer emulsion.

Benefits of technology

It significantly improves the high-temperature and low-temperature performance of the materials, extends the service life of the road, reduces road construction costs, reduces carbon emissions, and achieves environmental protection and economic benefits by absorbing wind-abundant sand resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263694A_ABST
    Figure CN119263694A_ABST
Patent Text Reader

Abstract

The invention discloses a water-based polymer emulsion stabilized fiber aeolian sand macadam base material and a preparation method, and belongs to the technical field of pavement building materials, the water-based polymer emulsion stabilized fiber aeolian sand macadam base material comprises a base material, a water-based polymer and basalt fiber; the base material comprises the following components in percentage by mass: 60-70% of graded broken stone; 30% to 40% of aeolian sand; by taking the mass of the base material as a standard, the coating also comprises 0.4-1% of water-based polymer emulsion; 1%-2% of basalt fiber; the water-based polymer emulsion stabilized fiber aeolian sand macadam base material has good mechanical properties, stability and durability, solves the problems of reflection cracks, ruts and other diseases of a traditional semi-rigid base, and prolongs the service life of a pavement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pavement building materials, in particular to a water-based polymer emulsion-stabilized fiber aeolian sand and gravel base material and a preparation method thereof. Background Art

[0002] With the current development trend of road structure in the world, the traditional cement stabilized crushed stone (gravel) semi-rigid base is prone to cracks and rutting due to high rigidity, low tensile strength, poor deformation resistance, etc., under the influence of temperature changes, humidity changes, traffic loads, etc., causing road damage. Water-based polymers, as a new type of road base polymer, are evenly dispersed on the surface of stable materials such as soil and stone through water as a conductive medium. After effective compaction and water volatilization, an organic mucous film is formed on the surface of soil and stone solid particles inside the road structure layer, firmly bonding them into a whole to form a flexible structural layer; water-based polymer emulsion stabilized crushed stone (gravel) base can completely solve the cracks and rutting diseases existing in the current semi-rigid base; it can extend the service life of the road; it can reduce costs and carbon emissions.

[0003] However, the existing water-based polymer emulsion stabilized gravel base is easy to peel off from the aggregate surface, thereby affecting the high and low temperature performance of the aggregate base; in addition, the manufacturing cost of the existing water-based polymer emulsion stabilized gravel base is relatively high, resulting in a high sputtering cost for the overall road, which is not conducive to the development of the road. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a water-based polymer emulsion stabilized fiber aeolian sand and gravel base material and a preparation method. The base material can meet the requirements of the "JTG / T F20-2015 Technical Specifications for Highway Pavement Base Construction" and has good mechanical properties and durability, thereby extending the service life of the pavement.

[0005] The present invention is achieved through the following technical solutions: A water-based polymer emulsion stabilized fiber aeolian sand and gravel base material, comprising a base material, a water-based polymer and basalt fiber; In terms of mass percentage, the base material includes 60%-70% graded crushed stone; 30%-40% aeolian sand; based on the mass of the base material, it also includes 0.4%-1% water-based polymer emulsion; and 1%-2% basalt fiber.

[0006] Preferably, the water-based polymer emulsion is polyethyl methacrylate.

[0007] Preferably, the polyethyl methacrylate has a solid content of 28-38%, a viscosity of 50-100 cps, and a specific gravity>1.0.

[0008] Preferably, the basalt fiber has a diameter of 5-45 μm and a length of 6-18 mm.

[0009] Preferably, the graded crushed stone is a skeleton-dense graded gravel.

[0010] A method for preparing a water-based polymer emulsion-stabilized fiber aeolian sand and gravel base material, comprising: diluting the water-based polymer emulsion to obtain a water-based polymer diluted solution; The graded crushed stone, aeolian sand and basalt fiber are uniformly stirred with the water-based polymer emulsion to obtain a water-based polymer emulsion stabilized fiber aeolian sand crushed stone material.

[0011] Preferably, according to the optimum water content of the water-based polymer emulsion and the graded crushed stone, the amount of water added to the water-based polymer emulsion corresponding to the optimum water content is determined, and the water-based polymer emulsion is diluted according to the amount of water added.

[0012] Preferably, a graded compaction test is used to determine the optimum moisture content of the water-based polymer emulsion and the graded crushed stone.

[0013] Preferably, the preparation of the water-based polymer emulsion stabilized fibrous aeolian sand and gravel material comprises: Firstly, graded crushed stone and aeolian sand are dry-mixed to obtain a mixture, then the mixture is mixed with a water-based polymer diluted solution, and finally basalt fiber is added and stirred to obtain a water-based polymer emulsion stabilized fiber aeolian sand crushed stone material.

[0014] A road comprises the water-based polymer emulsion stabilized fiber aeolian sand and gravel base material.

[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention provides a water-based polymer emulsion stabilized fiber aeolian sand and gravel base material. By adding an appropriate amount of basalt fiber, the basalt fiber plays a "reinforcement" role in the material, enhancing the tensile, shear and crack resistance of the material, making it uniformly dispersed in the water-based polymer emulsion stabilized aeolian sand and gravel during the mixing process, and finally forming a three-dimensional skeleton after paving and rolling. The fibers overlap each other, which has a strong reinforcement effect, and can lock the water-based polymer emulsion and aeolian sand and gravel firmly together, so that the water-based polymer emulsion is not easy to peel off from the aggregate surface, so that the low-temperature and high-temperature performance, water stability and tensile performance can be significantly improved. In addition, the present invention uses aeolian sand to absorb and process the abundant aeolian sand resources, reduce road construction costs, and save energy and protect the environment. The sand, which was originally worthless and polluted the environment, is turned into treasure by adding it as fine aggregate into the water-based polymer emulsion stabilized fiber wind-blown sand and gravel material. It can not only absorb and process a large amount of wind-blown sand resources, but also reduce engineering costs, contribute to ecological construction, alleviate resource crises, and bring economic and environmental benefits. The water-based polymer emulsion stabilized fiber wind-blown sand and gravel material is a kind of flexible base. Compared with traditional semi-rigid bases such as cement / lime stabilized gravel materials, it has its own strong and tough characteristics. It can disperse stress, reduce the impact of load on the base, increase road life, and reduce road diseases. It also has obvious advantages in cost, construction, road performance, and traffic relief.

[0016] Furthermore, the water-based polymer emulsion in the present invention is a polyethyl methacrylate water-based polymer emulsion. The water-based polymer is a binder material, is flexible and does not harden, has many advantages such as being environmentally friendly, economical, inhibiting the formation of cracks in the road surface, avoiding the formation of rutting, not requiring watering for curing, having a long storage time for the mixture, good waterproofing, short construction period, quick construction, simple equipment and a wide range of applications.

[0017] Furthermore, the use of dense skeleton grading for graded gravel can better bond the SRX water-based polymer and the fibrous aeolian sand gravel, making the mechanical properties and road performance of the material stronger.

[0018] The preparation method provided in the present application determines the optimal water content of the water-based polymer emulsion stabilized gravel according to the grading compaction test, and obtains the amount of water added after removing the water content of the water-based polymer emulsion. The density of the water-based polymer is close to that of water, and it can be regarded as water addition, eliminating the complicated and tedious calculation process. The preparation method has simple steps and can effectively improve the construction efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 The present invention is a flow chart of the water-based polymer emulsion stabilizing the fiber aeolian sand and gravel base material. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.

[0022] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0023] A water-based polymer emulsion stabilized fiber aeolian sand and gravel base material, comprising a base material, a water-based polymer and basalt fiber; Calculated by mass percentage, the base material includes crushed stone accounting for 60%-70%; aeolian sand as fine aggregate accounting for 30%-40%; based on the mass of the base material, 0.4%-1% of water-based polymer emulsion is added; and 1%-2% of basalt fiber.

[0024] The water-based polymer emulsion is polyethyl methacrylate (-[CH2CCH2-COOCH2CH3] n -), the properties of the water-based polymer emulsion are shown in Table 1.

[0025] Table 1

[0026] The basalt fiber is a short-cut basalt fiber with a nominal diameter of 5-45 μm and a nominal length of 6-18 mm.

[0027] The aeolian sand is used as fine aggregate, and its particle size is about 0.075mm-0.25mm. The technical requirements for coarse and fine aggregates meet the relevant provisions of Table 3.6.1 and Table 3.7.2 in "JTG / T F20-2015 Technical Specifications for Highway Pavement Base Construction".

[0028] The grading range of the graded crushed stone complies with the relevant provisions of Chapter 7.2.2 of "Q / T ROM001-2017 Design Standard for Polymer Flexible Road Structure for Road Use" or Table 3.2.1 of "Q / T ROM002-2017 Technical Specifications for Construction of Polymer Road Base for Road Use".

[0029] The grading range of the present invention has the following advantages: (1) The pass rate of 0.075 mm is 5% to 10%, which ensures the stability of the mixed material performance; and the pass rate is ≥5%, which can better ensure the density; the pass rate ≤10% has a small specific surface area, which is suitable for the material characteristics of low curing agent dosage. (2) The pass rate of 4.75-0.3 mm fine material pore size is generally low, and the specific surface area is small, which is suitable for the material characteristics of low curing agent dosage. (3) The pass rate of coarse material above 4.75 mm is generally high and the grading curve is smoother, which is beneficial to the density and uniformity of the mixed material, thereby improving the strength and fatigue performance. Basalt fiber is a man-made fiber material made of basalt quartz fiber. It is a new type of green, environmentally friendly and pollution-free inorganic non-metallic mineral fiber with excellent chemical stability, high temperature resistance, wear resistance, high strength and elongation. Aeolian sand has a stable chemical composition and hidden value, which can alleviate the resource crisis and bring economic and environmental benefits.

[0030] The water-based polymer emulsion stabilized fiber wind-blown sand gravel material first overcomes the shortcomings and deficiencies of the traditional semi-rigid base, and has good stability and durability on the premise of having good mechanical properties; secondly, the added basalt fiber acts as a "reinforcement" in the mixture, enhancing the overall crack resistance of the material; finally, by adding wind-blown sand to turn waste into treasure, it achieves the effect of reducing costs and protecting the environment. The material of the present invention is environmentally friendly, the preparation method is simple, the equipment used is cheap, and the mixing at room temperature does not require heating. It truly improves the defects of the previous invention of inorganic / organic material stabilized gravel and accelerates the localization application of water-based polymer emulsion stabilization technology.

[0031] The water-based polymer emulsion stabilized gravel base can completely solve the cracks and rutting diseases existing in the current semi-rigid base; it can extend the service life of the road; it can reduce costs and carbon emissions. Basalt fiber is a man-made fiber material made of basalt quartz fiber. It is a new type of green, environmentally friendly, and pollution-free inorganic non-metallic mineral fiber with excellent chemical stability, high temperature resistance, wear resistance, high strength and elongation. Aeolian sand has a stable chemical composition and hidden value, which can alleviate the resource crisis and bring economic and environmental benefits. Therefore, in view of the advantages of the above materials, this application proposes a new type of water-based polymer emulsion stabilized fiber aeolian sand gravel (gravel) base material, which meets the specifications of the "JTG / TF20-2015 Technical Specifications for Highway Pavement Base Construction" and has good mechanical properties and durability, extending the service life of the road surface.

[0032] Correspondingly, the present application also provides a method for preparing the above-mentioned water-based polymer emulsion stabilized fiber aeolian sand and gravel base material, comprising the following steps: Step 1, preparing graded crushed stone; The graded crushed stone is prepared according to the recommended gradation range in Chapter 7.2.2 of "Q / T ROM001-2017 Design Standard for Polymer Flexible Road Structure for Road Use" or Table 3.2.1 of "Q / T ROM002-2017 Technical Specification for Construction of Polymer Road Base for Road Use", and the entire preparation process is carried out at room temperature.

[0033] Step 2, determining the optimum moisture content of the water-based polymer emulsion and the graded crushed stone; The optimum moisture content is determined by a graded compaction test, and the amount of water added is obtained after removing the amount of water-based polymer emulsion added.

[0034] Step 3: diluting the water-based polymer emulsion according to the optimal water content to obtain a water-based polymer diluted solution.

[0035] The amount of water added is determined according to the optimum moisture content, the water-based polymer emulsion is added to the mixing pot, and then a determined amount of water is added to dilute the water-based polymer emulsion. When the water-based polymer emulsion and water in the mixing pot are evenly mixed, the stirring is stopped to obtain a water-based polymer diluted solution.

[0036] Step 4: Evenly stir the graded crushed stone, aeolian sand and basalt fiber with the water-based polymer emulsion to obtain a water-based polymer emulsion-stabilized fiber aeolian sand crushed stone material.

[0037] First, add graded gravel and aeolian sand into a mixing pot and dry mix for 3-5 minutes. Then add the water-based polymer emulsion obtained in step 3 and mix and stir evenly with the aeolian sand and gravel until the mixture is uniform. Then, add basalt fiber. After the basalt fiber is evenly distributed in the mixture, a water-based polymer emulsion-stabilized fiber aeolian sand and gravel material is obtained.

[0038] Example 1 A water-based polymer emulsion stabilized fiber aeolian sand and crushed stone base material comprises, by percentage, 0.5% of water-based polymer emulsion, 1% of basalt short-cut fiber, 60% of graded crushed stone, and 40% of aeolian sand as fine aggregate.

[0039] The technical indicators of the water-based polymer emulsion are as follows: see Table 2.

[0040]

[0041] The crushed stone adopts Xinjiang Urumqi broken gravel, which has a crushing value of 15%, Los Angeles abrasion loss of 18.4%, firmness of 5%, needle-like particle content of 10.6% in the gravel, and dust content below 0.075mm of 0.17%.

[0042] Aeolian sand was collected from the Gurbantunggut Desert, with an apparent relative density of 2.78 g cm -3 , angularity 41.7S.

[0043] The basalt fiber selected was short-cut basalt fiber with a length of 6 mm and a diameter of 13 μm produced by Henan Dengdian Basalt Fiber Co., Ltd. The technical parameters are shown in Table 3.

[0044]

[0045] The gradation of crushed stone is shown in Table 4

[0046] According to the grading compaction test, the optimal moisture content of water-based polymer stabilized crushed stone is 4.4%, and the maximum dry density is 2.27g / cm 3 .

[0047] The grading range has the following advantages: (1) The pass rate of 0.075mm is 5% to 10%, ensuring the stability of the mixture performance; and the pass rate is ≥5%, which can better ensure the density; the pass rate ≤10% has a small specific surface area, which is suitable for the characteristics of materials with low curing agent usage. (2) The pass rate of 4.75-0.3mm fine material pore size is generally low, and the specific surface area is small, which is suitable for the characteristics of materials with low curing agent usage. (3) The pass rate of coarse material above 4.75mm is generally high and the grading curve is smoother, which is beneficial to the density and uniformity of the mixture, thereby improving strength and fatigue performance.

[0048] The preparation method of the water-based polymer emulsion stabilized fiber wind-blown sand and gravel base material is as follows: Step 1: According to the grading range in Table 4, graded crushed stone (gravel) is batched using standard materials. The entire preparation process is carried out at room temperature to obtain graded crushed stone.

[0049] Step 2, first add the water-based polymer emulsion into the mixing pot, determine the amount of water to be added according to the optimum water content, then add water to dilute the water-based polymer emulsion, and stop stirring when the water-based polymer emulsion and water in the stirring pot are evenly mixed to obtain a water-based polymer diluted solution; Step 3: Add graded gravel and aeolian sand into a stirring pot and dry mix for 3-5 minutes, then add the diluted water-based polymer solution and mix and stir evenly with the aeolian sand and gravel until the color of the mixture is consistent after mixing, then add basalt fiber, and after the basalt fiber is evenly distributed in the mixture, mix and stir for 5-10 minutes to obtain a water-based polymer emulsion stabilized fiber aeolian sand and gravel material.

[0050] The CBR test uses the static pressure method to form specimens, and the test steps refer to "JTG 3430-2020 Highway Geotechnical Test Code"; the penetration strength test uses the static pressure method to form specimens, and the test steps refer to "JTG D50-2017 Highway Asphalt Pavement Design Specification Appendix F"; the dynamic triaxial compression test uses the static pressure method to form specimens, and the test steps refer to "AASHTO Designation T 307-99 (2003)".

[0051] The performance test results of this embodiment are shown in Table 5.

[0052] Example 2 A water-based polymer emulsion stabilized fiber aeolian sand and crushed stone base material comprises, by percentage, 0.4% of water-based polymer emulsion, 1% of basalt chopped fibers, 60% of graded crushed stones, and 40% of aeolian sand as fine aggregate.

[0053] The types and performance indicators of the raw materials in this embodiment are the same as those in Example 1, and the preparation is carried out by the same preparation method as in Example 1. The performance test results of the obtained water-based polymer emulsion stabilized fiber aeolian sand and gravel base material are shown in Table 5.

[0054] Example 3 A water-based polymer emulsion stabilized fiber aeolian sand and crushed stone base material comprises, by percentage, 0.6% of water-based polymer emulsion, 1% of basalt chopped fibers, 60% of graded crushed stones, and 40% of aeolian sand as fine aggregate.

[0055] The types and performance indicators of the raw materials in this embodiment are the same as those in Example 1, and the preparation is carried out by the same preparation method as in Example 1. The performance test results of the obtained water-based polymer emulsion stabilized fiber aeolian sand and gravel base material are shown in Table 5.

[0056] Example 4 A water-based polymer emulsion stabilized fiber aeolian sand crushed stone base material comprises, by percentage, 1% water-based polymer emulsion, 1% basalt short-cut fiber, 60% graded crushed stone, and 40% aeolian sand as fine aggregate.

[0057] The types and performance indicators of the raw materials in this embodiment are the same as those in Example 1, and the preparation is carried out by the same preparation method as in Example 1. The performance test results of the obtained water-based polymer emulsion stabilized fiber aeolian sand and gravel base material are shown in Table 5.

[0058] Example 5 A water-based polymer emulsion stabilized fiber aeolian sand and gravel base material comprises, by percentage, 0.4% of water-based polymer emulsion, 2% of basalt chopped fibers, 60% of graded gravel, and 40% of aeolian sand as fine aggregate.

[0059] The types and performance indicators of the raw materials in this embodiment are the same as those in Example 1, and the preparation is carried out by the same preparation method as in Example 1. The performance test results of the obtained water-based polymer emulsion stabilized fiber aeolian sand and gravel base material are shown in Table 5.

[0060] Example 6 A water-based polymer emulsion stabilized fiber aeolian sand and crushed stone base material comprises, by percentage, 0.5% of water-based polymer emulsion, 2% of basalt chopped fibers, 60% of graded crushed stones, and 40% of aeolian sand as fine aggregate.

[0061] The types and performance indicators of the raw materials in this embodiment are the same as those in Example 1, and the preparation is carried out by the same preparation method as in Example 1. The performance test results of the obtained water-based polymer emulsion stabilized fiber aeolian sand and gravel base material are shown in Table 5.

[0062] Example 7 A water-based polymer emulsion stabilized fiber aeolian sand and crushed stone base material comprises, by percentage, 0.6% of water-based polymer emulsion, 2% of basalt chopped fibers, 65% of graded crushed stones, and 35% of aeolian sand as fine aggregate.

[0063] The types and performance indicators of the raw materials in this embodiment are the same as those in Example 1, and the preparation is carried out by the same preparation method as in Example 1. The performance test results of the obtained water-based polymer emulsion stabilized fiber aeolian sand and gravel base material are shown in Table 5.

[0064] Example 8 A water-based polymer emulsion stabilized fiber aeolian sand and crushed stone base material comprises, by percentage, 1% of water-based polymer emulsion, 1.5% of basalt chopped fibers, 70% of graded crushed stones, and 30% of aeolian sand as fine aggregate.

[0065] The types and performance indicators of the raw materials in this embodiment are the same as those in Example 1, and the preparation is carried out by the same preparation method as in Example 1. The performance test results of the obtained water-based polymer emulsion stabilized fiber aeolian sand and gravel base material are shown in Table 5.

[0066] Comparative Example 1: A base material comprises, by mass percentage, 60% graded crushed stone and 40% aeolian sand fine material.

[0067] The performance test results of the base material are shown in Table 5.

[0068] Table 5

[0069] It can be seen from Table 5 that the bearing capacity, shear deformation resistance and dynamic modulus parameters of a water-based polymer emulsion stabilized fiber aeolian sand and gravel base material of the present application are greatly improved. It can be seen that increasing the amount of water-based polymer and basalt fiber can not only enhance the strength of the stabilized gravel (gravel) material, but also can absorb the treated aeolian sand, thus achieving the advantages of energy saving, environmental protection, economic applicability and excellent performance.

[0070] A road comprises the water-based polymer emulsion stabilized fiber aeolian sand and gravel base material.

[0071] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A water-based polymer emulsion stabilized fiber aeolian sand and gravel base material, characterized in that: including a substrate, a water-based polymer, and basalt fibers; In terms of mass percentage, the base material includes 60%-70% graded crushed stone; 30%-40% aeolian sand; based on the mass of the base material, it also includes 0.4%-1% water-based polymer emulsion; and 1%-2% basalt fiber.

2. The water-based polymer emulsion stabilized fiber aeolian sand and gravel base material according to claim 1, characterized in that: The water-based polymer emulsion is polyethyl methacrylate.

3. The water-based polymer emulsion stabilized fiber aeolian sand and gravel base material according to claim 2, characterized in that: The polyethyl methacrylate has a solid content of 28-38%, a viscosity of 50-100 cps, and a specific gravity>1.

0.

4. The water-based polymer emulsion stabilized fiber aeolian sand and gravel base material according to claim 1, characterized in that: The basalt fiber has a diameter of 5-45 μm and a length of 6-18 mm.

5. The water-based polymer emulsion stabilized fiber aeolian sand and gravel base material according to claim 1, characterized in that: The graded crushed stone is a skeleton-dense gradation.

6. A method for preparing a water-based polymer emulsion stabilized fibrous aeolian sand and gravel base material according to any one of claims 1 to 5, characterized in that: include: diluting the water-based polymer emulsion to obtain a water-based polymer diluted solution; The graded crushed stone, aeolian sand and basalt fiber are uniformly stirred with the water-based polymer emulsion to obtain a water-based polymer emulsion stabilized fiber aeolian sand crushed stone material.

7. The method for preparing a water-based polymer emulsion stabilized fiber aeolian sand and gravel base material according to claim 6, characterized in that: According to the optimum moisture content of the water-based polymer emulsion and the graded crushed stone, the amount of water added to the water-based polymer emulsion corresponding to the optimum moisture content is determined, and the water-based polymer emulsion is diluted according to the amount of water added.

8. The method for preparing a water-based polymer emulsion stabilized fiber aeolian sand and gravel base material according to claim 7, characterized in that: The graded compaction test was used to determine the optimum moisture content of water-based polymer emulsion and graded crushed stone.

9. The method for preparing a water-based polymer emulsion stabilized fiber aeolian sand and gravel base material according to claim 6, characterized in that: The preparation of the water-based polymer emulsion stabilized fiber aeolian sand and gravel material comprises: Firstly, graded crushed stone and aeolian sand are dry-mixed to obtain a mixture, then the mixture is mixed with a water-based polymer diluted solution, and finally basalt fiber is added and stirred to obtain a water-based polymer emulsion stabilized fiber aeolian sand crushed stone material.

10. A road, characterized in that: The invention comprises a water-based polymer emulsion-stabilized fiber aeolian sand and gravel base material as described in any one of claims 1 to 5.